2021
DOI: 10.1093/jb/mvab109
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNA AFAP1-AS1 promotes thyroid cancer progression by sponging miR-204-3p and upregulating DUSP4

Abstract: Long non-coding RNA (lncRNA) actin filament-associated protein 1-antisense RNA 1 (AFAP1-AS1), shows crucial regulatory function in tumor progression. Nonetheless, the biological function and underlying mechanism of AFAP1-AS1 in the progression of thyroid cancer is still unclear. Expressions of AFAP1-AS1, miR-204-3p, and DUSP4 were quantified utilizing qRT-PCR and/or Western blot. In loss-of-function and gain-of-function assays, cell proliferation, migration and invasion were appraised by CCK-8 assay, wound hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[15] Numerous studies have also shown that AFAP1-AS1 is often dysregulated in various human cancers, including thyroid, lung, and breast cancer, as well as osteosarcoma and PA, and its aberrant expression regulates numerous hallmarks to promote tumor development, invasion, and metastasis, such as proliferation, apoptosis, metastasis, and glycolysis. [12,13,[23][24][25][26] In PA, downregulation of AFAP1-AS1 impeded cell proliferation, growth hormone and prolactin secretion, and induced cell apoptosis and G/S cell cycle arrest. [13] In the present study, we found that AFAP1-AS1 was signi cantly upregulated in cells treated with exosomes derived from PA.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Numerous studies have also shown that AFAP1-AS1 is often dysregulated in various human cancers, including thyroid, lung, and breast cancer, as well as osteosarcoma and PA, and its aberrant expression regulates numerous hallmarks to promote tumor development, invasion, and metastasis, such as proliferation, apoptosis, metastasis, and glycolysis. [12,13,[23][24][25][26] In PA, downregulation of AFAP1-AS1 impeded cell proliferation, growth hormone and prolactin secretion, and induced cell apoptosis and G/S cell cycle arrest. [13] In the present study, we found that AFAP1-AS1 was signi cantly upregulated in cells treated with exosomes derived from PA.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs play a regulatory role in tumors by functioning as miRNA sponges to competitively regulate the miRNA-targeted genes, also known as the competing endogenous RNA (ceRNA) mechanism. In thyroid cancer, AFAP1-AS1, TNRC6C-AS1, and LINC00284 regulate cancer occurrence and progression by sponging miR-204-3p, miR-513c-5p, and miR-30d-5p, respectively [ 13 15 ]. LINC00894 can sponge miR-429 to promote the progression of breast cancer [ 11 ].…”
Section: Introductionmentioning
confidence: 99%